Synthesis and Characterization of Transition Metal Complexes with 7-(R)-2-Amino-2- (4-hydroxyphenyl)acetamido]-3-methyl-3-cephem-4-carboxylic Acid Monohydrate - Deshmukh, J.H.; Deshpande, M.N. (Asian Journal of Chemistry, 2010)
7-(R)-2-Amino-2-(4-hydroxyphenyl)acetamido]-3-methyl-3-cephem-4-carboxylic acid monohydrate (AMCC) is a active chelating agent due to presence of different donor atoms. When this chelating agent is treated with Fe2+, Co2+ and Cu2+ metal ion solution at specific pH it produces different metal ion complexes, after purification they were characterized by physical and chemical methods. To determine the nature of bonding in the complexes infrared, UV-Visible, ESR spectra are used. TGA-DTA gives information regarding effect of temperature in the decomposition of complexes. XRD and other parameters are used for determining probable geometry of metal complexes.